Advokasi Kebijakan Kesehatan Lingkungan Berbasis Masyarakat di Desa Sambelia Lombok Timur - Fathul Azmi; Riasari Mardani; Dhandi Hidayatullah; Mohamad Ariansidi; Muhammad Junaedi (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
Community-based environmental health advocacy in rural Indonesia remains underdeveloped, particularly in remote coastal villages with limited sanitation infrastructure. This community service aimed to identify dominant environmental health problems, implement participatory policy advocacy, and produce a policy brief as a formal recommendation for village government. Using a qualitative approach with with case study design and participatory action research (PAR), data were collected through in-depth interviews, participatory observation, and documentation study involving 15 purposively selected informants comprising village officials, health cadres, community leaders, PKK representatives, and community health center officers. Rapid assessment revealed that 74% of households lacked adequate domestic wastewater management, 68% practiced improper solid waste disposal, 55% experienced limited clean water access, and 38% still engaged in open defecation. Advocacy capacity building carried out through focused group discussions, advocacy training, and policy brief mentoring successfully shifted the community paradigm from passive recipients to active policy agents. The policy brief produced through participatory processes secured a formal commitment from the village head to incorporate communal sanitation programs into the Village Government Work Plan (RKPDes). This model demonstrates that integrating field-based problem identification through rapid assessment, community advocacy capacity building, and structured formal recommendation mechanisms can effectively stimulate concrete and sustainable policy responses at the village level.